Jesus the apocalyptic prophet - Wassen, Cecilia (T&T Clark, 2020)
"This book is a reconstruction of the life of Jesus from his birth to his death, with a focus on understanding him in the context of his own time and place. Wassen and Hägerland consider Jesus as an apocalyptic prophetic figure within the context of first-century Judaism. They take a narrative approach, examining Jesus' life in order and draw together the threads of scholarly discussion on the history, archaeology and geography of first-century Galilee into a complete picture of Jesus' world suitable for a non-specialist audience. Together the chapters provide a deeply informed introduction to Jesus in his first-century context. The authors follow a scientific worldview for historical reconstruction, drawing readers' attention to the rhetorical aspects of the texts of the New Testament and problematising these elements. They embed the texts surrounding Jesus in the context of first-century Galilee with historical and archaeological reflections and discussion and, in particular, with penetrating insights from the Dead Sea Scrolls. Illustrated throughout with photographs taken by the authors specifically to offer insights into the world of Jesus and the New Testament writings"--